(untitled) (Journal of Hama University, 2024)
Aim of this study was to evaluate the effect of Ibuprofen on the efficacy of Inferior alveolar nerve block injection for treatment of lower Primary molars with irreversible pulpitis. The research sample consist of 80 children in the age group 6-9 years, who had not previous bad dental experience, they were rated as (+) or (++) based on Frankl behavior rating scale, they were rated as (I) based on American Society of Anesthesiologists classification and they had lower primary molar (first or second primary molar) with irreversible pulpitis that need pulpectomy. The sample is divided into 4 groups based on the administered drug and the local anesthetic agent that have been used in the inferior alveolar nerve block: the first group is Ibuprofen/Lidocaine, the second is Ibuprofen/Mepvicaine, the third group is Placebo/Lidocaine and the fourth group is Placebo/Mepvicaine. Pain was assessed in each group during access cavity preparation and initial canals preparation by using Face Pain Scale Revised(FPS-R) Results: The result of our study has shown significant deference at confidence level 95% (p<0.05) between all groups, the less pain level was for Ibuprofen/Lidocaine group, then Ibuprofen/Mepvicaine, Placebo/ Mepvicain , and Placebo/Lidocaine groups respectively. Furthermore it has shown no significant deference at confidence level 95% (p>0.05) between Ibuprofen/Lidocaine and Ibuprofen/Mepvicaine groups and between Placebo/lidocaine and Placebo/ Mepvicaine groups. The mean values of Face pain scale revised for each group was (Lidocaine/Placebo=4.9, lidocaine/Ibuprofen=1.1, Mepvicaine/Placebo=1.2, Mepvicaine/Placebo=4.9) during Access cavity preparation and ( Lidocaine/Placebo=4.6, Lidocaine/Ibuprofen=1, Mepvicaine/Ibuprofen=1.3, Mepvicaine/Placebo=4.5) during initial canals preparation. It was noted that oral administration of Ibuprofen before 1 hour of Inferior alveolar nerve block (IANB) injection by using of Lidocaine 2% with1:80.000 epinpherene or Mepvicaine 3% without vasoconstrictor have raised its efficacy and resulting in less pain for FPS-R during treatment of lower primary molars with irreversible pulpitis. In addition there is no significant deference between Lidocaine and Mepvicaine in their efficacy in Inferior alveolar nerve block injection for treatment of Lower Primary molars with Irreversible pulpitis.